An Experimental Study of Mechanical Properties of Class G Cement Sheath in the Niger Delta - Etoh, J.O.; Dosunmu, A. (My University, 2021)
There are three basic components of a wellbore system, namely: Casing, Cement sheath and Rock formation. Although the cement sheath serves multiple purposes in the wellbore, its basic function is to act as a well barrier such that wellbore integrity is maintained. As a well barrier, it prevents unintentional and uncontrollable fluid flow from one formation into another of back to the surface. However, during drilling and production operations, the cement is subjected to various stresses resulting from thermal stress, non-uniform geo-stress, compressive and tensile stresses etc. Previously the main mechanical property of cement that was measured was the compressive strength, but now focus is also shared to other properties such as flexural strength, rupture elongation percentage, young’s modulus and poissons ratio. The purpose of this paper is to test experimentally the response of the cement sheath to various loads and determine its ability to resist energy/stress application. Class G cement with varying water-cement ratio (0.4, 0.5 and 0.6) were cured and tested for its mechanical properties.
International Journal of Engineering Science Invention (IJESI) Volume 10 Issue 10 Series II
Keywords: Cement; Mechanical properties; Wellbore Integrity; STEM; University of Port Harcourt; ACEcOR